A novel in silico minigene vaccine based on CD4+ T-helper and B-cell epitopes of EG95 isolates for vaccination against cystic echinococcosis. (February 2018) - Pourseif, Mohammad M.; Moghaddam, Gholamali; Naghili, Behrouz; Saeedi, Nazli; Parvizpour, Sepideh; Nematollahi, Ahmad; Omidi, Yadollah
Graphical abstract: Highlights: An in silico multiepitope sheep-specific vaccine was designed based on ovar MHC class II alleles. Comprehensive computational methodologies was applied for the construction of minigene vaccine against E. granulosus . In silico epitope mapping tools were used for the identification of B-cell and helper T-cell epitopes. Various sequences of Eg95 from different geographical regions was used for greater coverage. Abstract: EG95 oncospheral antigen plays a crucial role in Echinococcus granulosus pathogenicity. Considering the diversity of antigen among different EG95 isolates, it seems to be an ideal antigen for designing a universal multivalent minigene vaccine, so-called multi-epitope vaccine. This is the first in silico study to design a construct for the development of global EG95-based hydatid vaccine against E. granulosus in intermediate hosts. After antigen sequence selection, the three-dimensional structure of EG95 was modeled and multilaterally validated. The preliminary parameters for B-cell epitope prediction were implemented such as the possible transmembrane helix, signal peptide, post-translational modifications and allergenicity. The high ranked linear and conformational B-cell epitopes derived from several online web-servers (e.g., ElliPro, BepiPred v 1.0, BcePred, ABCpred, SVMTrip, IEDB algorithms, SEPPA v 2.0 and Discotope v 2.0) were utilized for multiple sequence alignment and then for engineering the vaccine construct. T-helper based epitopes were predicted by molecular docking between the high frequent ovar class II allele (Ovar-DRB1*1202) and hexadecamer fragments of the EG95 protein. Having used the immune-informatics tools, we formulated the first EG95-based minigene vaccine based on T-helper epitope with high-binding affinity to the ovar MHC allele. This designed construct was analyzed for different physicochemical properties. It was also codon-optimized for high-level expression in Escherichia coli k12. Taken all, we propose the present in silico vaccine constructs as a promising platform for the generation of broadly protective vaccines for species and genus-specific immunization of the natural hosts of the parasite.